Comorbid medical conditions in young athletes: Considerations for preparticipation guidance during the COVID-19 pandemic - Harmon, K. G.; Pottinger, P. S.; Baggish, A. L.; Drezner, J. A.; Luks, A. M.; Thompson, A. A.; Swaminathan, S. (Sports Health: A Multidisciplinary Approach, 2020)
Young athletes, generally speaking, represent one of the healthiest and fittest groups in society. The resumption of sport and exercise will ultimately bring athletes into closer proximity than is recommended by current physical distancing practices, potentially increasing one`s risk of infection. Data are emerging that high-intensity exercise may increase aerosolization and transmissibility of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) from presymptomatic and mildly symptomatic individuals. It is in this setting that medical providers have wondered how to best counsel athletes with medical conditions that may be associated with increased risk of severe coronavirus disease (COVID-19), specifically, diabetes, asthma, sickle cell trait (SCT), hypertension, and obesity. The Centers for Disease Control and Prevention (CDC) guidance does not explicitly address young athletes returning to sport but recommends that high-risk individuals of any age take extra precautions, including those with chronic lung disease or moderate to severe asthma, chronic kidney disease being treated with dialysis, diabetes mellitus, hemoglobin disorders, liver disease, serious heart conditions, severe obesity (body mass index [BMI] =40 kg/m2), or who are immunocompromised. There is limited epidemiologic evidence to inform guidance for such individuals, especially in the high school and college age groups; however, young people in general are at low risk for poor outcomes including death, hospitalization, and severe disease. Here, we offer our appraisal of the situation and provide information that may help frame discussions with athletes.